The six myths of healthcare privatization - de Montalvo Jääskeläinen, Federico (Razón y fe, 2018)
Health, one of the rights of the Welfare State, is being harassed in Spain and in the West by the economic crisis. Many Spaniards fear for our current healthcare system. The media consciously, sometimes unconsciously, have woven a series of myths around health that defend always interested and ambiguous purposes that are difficult to refute. The six myths about health that are exposed in this article, and strive to be a reasoned and judicious proposal of our political and social reality.